2023
DOI: 10.1177/25160435231213296
|View full text |Cite
|
Sign up to set email alerts
|

How deep is a problem of second victims for medical staff? A pilot study in Croatia

Anatoliy G Goncharuk,
Bojana Knežević,
Sandra C Buttigieg
et al.

Abstract: Adverse events lead to the emergence of several groups of victims, among which the second victims are medical staff involved in them. The suffering of second victims can lead to new adverse events and new victims. This study describes the cycle of an adverse event and its victims. Using the example of the largest Croatian hospital centre, authors try to understand how deep medical staff experience adverse events, and how different groups of medical staff (by profession, gender, qualification, and position) per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…After an adverse event, the prevalence of second victims varied from 10.4% up to 43.3%.9. (Goncharuk 2023).Research has shown that almost half of HCPs experience the impact as an SV at least one time in their career Ozeke (2019). Indeed, there are always SVs, when there is a serious patient adverse event, but mostly silent because of the fear of litigation and the absence of a welldefined reporting system (Edrees 2011).…”
Section: Prevalence Of Healthcare Professionals As Second Victims Of ...mentioning
confidence: 99%
“…After an adverse event, the prevalence of second victims varied from 10.4% up to 43.3%.9. (Goncharuk 2023).Research has shown that almost half of HCPs experience the impact as an SV at least one time in their career Ozeke (2019). Indeed, there are always SVs, when there is a serious patient adverse event, but mostly silent because of the fear of litigation and the absence of a welldefined reporting system (Edrees 2011).…”
Section: Prevalence Of Healthcare Professionals As Second Victims Of ...mentioning
confidence: 99%
“…Goncharuk et al 8 studied the problem of second victims in Croatia. They expressed the need for active medical workers trained in supporting clinicians after adverse events.…”
mentioning
confidence: 99%